The 9th man - Berry, Steve, 1955-; Blackwood, Grant (A Luke Daniels thriller, 2023)
"Luke Daniels is in London, between assignments with the Magellan Billet, when he receives a frantic call from an old friend. Jillian Stein is in trouble. She made a mistake and now her life may be in danger. She needs Luke's help. Immediately. Racing to Belgium, Luke quickly finds that she was right. A shadow team of highly trained operatives is there on the hunt. Intervening, he finds himself embroiled in a war between two determined sides--one seeking the truth, the other trying to escape the past--a war that has already claimed one life and is about to claim more. Thomas Rowland is a Washington insider, a kingmaker, problem solver, but also a man with a past. For him everything turns with what happened on November 22, 1963 in Dallas, Texas. What history has recorded is wrong. There is more to the story, much more, and Thomas Rowland is at the center of that terrible reality. But forces are working against him, and Rowland will do anything to keep the world from learning what actually happened on that fateful day, including killing Luke, Jillian and anyone else who might be a threat. In a race from Belgium, to Luxembourg, to the bayous of Louisiana and the Wyoming wilderness, to a final confrontation in the Bahamas, Luke Daniels confronts a series of shocking truths which not only rewrite history but will forever change his own life--as he comes face to face with the ninth man"--